2018
DOI: 10.12688/f1000research.13457.1
|View full text |Cite
|
Sign up to set email alerts
|

Successful CRISPR/Cas9 mediated homologous recombination in a chicken cell line

Abstract: CRISPR/Cas9 system is becoming the dominant genome editing Background: tool in a variety of organisms. CRISPR/Cas9 mediated knock out has been demonstrated both in chicken cell lines and in chicken germ cells that served to generate genetically modified birds. However, there is limited data about CRISPR/Cas9 dependent homology directed repair (HDR) for avian, even in cell culture. Few attempts have been made with integrations in safe harbor loci of chicken genome that induces constitutive expression of the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…However, our results showed that the T7E1 assay almost couldn't detect positive cells in the groups without puromycin selection. In the groups with puromycin selection, the T7E1 assay detected 12.9–72.1% indels, which was similar to the results of the previous reports ( Abu-Bonsrah et al, 2016 ; Bai et al, 2016 ; Antonova et al, 2018 ). The performance of T7E1 may be impacted by the length and identity of base pair mismatches, flanking sequence, secondary structure, and relative abundance of mutant sequence ( Vouillot et al, 2015 ; Michalski et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results showed that the T7E1 assay almost couldn't detect positive cells in the groups without puromycin selection. In the groups with puromycin selection, the T7E1 assay detected 12.9–72.1% indels, which was similar to the results of the previous reports ( Abu-Bonsrah et al, 2016 ; Bai et al, 2016 ; Antonova et al, 2018 ). The performance of T7E1 may be impacted by the length and identity of base pair mismatches, flanking sequence, secondary structure, and relative abundance of mutant sequence ( Vouillot et al, 2015 ; Michalski et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In general, affected by transfection, cleavage, and repair efficiencies of the CRISPR/Cas9 system, most cells will not be induced with intent mutations at target sites ( Kim et al, 2011 ; Ren et al, 2015 ). Thus, simple methods for enriching cells with desired genetic modification are essential to facilitate genome editing in living cells ( Yan et al, 2016 ; Zhou et al, 2016 ; Antonova et al, 2018 ). For this approach, we used an RPG surrogate reporter in the present study based on antibiotic selection to enrich cells with gene mutations.…”
Section: Discussionmentioning
confidence: 99%